Analyses of more than 60, 000 exomes questions the role of numerous genes previously associated with dilated cardiomyopathy. Issue 6 (17th September 2016) - Nouhravesh, Nina; Ahlberg, Gustav; Ghouse, Jonas; Andreasen, Charlotte; Svendsen, Jesper H.; Haunsø, Stig; Bundgaard, Henning; Weeke, Peter E.; Olesen, Morten S.
Abstract: Background: Hundreds of genetic variants have been described as disease causing in dilated cardiomyopathy (DCM). Some of these associations are now being questioned. We aimed to identify the prevalence of previously DCM associated variants in the Exome Aggregation Consortium (ExAC), in order to identify potentially false‐positive DCM variants. Methods: Variants listed as DCM disease‐causing variants in the Human Gene Mutation Database were extracted from ExAC. Pathogenicity predictions for these variants were mined from dbNSFP v 2.9 database. Results: Of the 473 DCM variants listed in HGMD, 148 (31%) were found in ExAC. The expected number of individuals with DCM in ExAC is 25 based on the prevalence in the general population. Yet, 35 variants were found in more than 25 individuals. In 13 genes, we identified all variants previously associated with DCM; four genes contained variants above our estimated cut‐off. Prediction tools found ExAC variants to be significantly more tolerated when compared to variants not found in ExAC ( P  = 0.004). Conclusion: In ExAC, we identified a higher genotype prevalence of variants considered disease‐causing than expected. More importantly, we found 13 genes in which all variants previously associated with DCM were identified in ExAC, questioning the association of these genes with the monogenic form of DCM. Abstract : Of the 473 DCM variants listed in HGMD, 148 variants were found in ExAC. The genotype prevalence of DCM variants in ExAC was higher than 1:2500, which is the expected prevalence of DCM. The association of 13 genes with the monogenic form of DCM was seriously questioned.